Expanding Spatial Understanding through Mobile Augmented Reality: A Contemporary Synthesis of Pedagogical, Technological, and Cognitive Dimensions in Geography Education - M. Iqbal Liayong Pratama; Daud Yusuf; Sri Maryati; Rusiyah Rusiyah; Wiwin Kobi; Ramla Hartini Melo; Moch Rio Pambudi; Masruroh Masruroh; Hendra Hendra; Asrul Asrul (Geosfera: Jurnal Penelitian Geografi, 2025)
Mobile augmented reality (AR) has evolved from an experimental visualization tool into a mature pedagogical medium that redefines spatial learning in geography education. By embedding digital content into authentic locations, AR fosters experiential and inquiry-driven learning aligned with geography’s spatial and environmental paradigms. Building on evidence from 2015 to 2025, this review synthesizes 138 studies to examine how AR supports cognitive, affective, and behavioral learning dimensions. The analysis reveals that AR enhances spatial reasoning, visualization of abstract processes, and place-based engagement when integrated within robust instructional design frameworks. However, persistent gaps remain in long-term learning assessment, scalability, and teacher competence for authoring AR experiences. Cognitive-load and motivation studies suggest that AR’s benefits are maximized when interactivity and spatial anchoring are balanced with scaffolding. The review proposes a multidimensional model linking technological affordances, pedagogical strategies, and geographic thinking to promote education for sustainability and digital spatial citizenship. Implications for researchers, educators, and developers are discussed to guide future cross-disciplinary innovations.